Experimental investigation of the performance of a household refrigerator using plywood as radiation shield - Mukhtar, U. A.; Shodiya, S.; Abdulrahaman, S. A.; Samuel, V. C.; Muhammed, A.; Maigida, A. Y. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
This research work investigates the performance of domestic refrigerators. Test were carried out on two configurations of household refrigerators; a conventional refrigerator and a refrigerator that was modified by incorporating a radiation shield. In this work, plywood was used as thermal radiation shield placed between the back of the refrigerator and the condenser and compressor. Pressure gauges were welded to the evaporator inlet and condenser outlet. Thermocouples were attached to the compressor inlet and outlet, condenser outlet and evaporator inlet in order to obtain data from the test. The pressure and temperature data obtained was applied to evaluate the performance of the two systems. With further repeated tests, the coefficient of performance (COP) of the refrigeration systems were determined at normal ambient condition. The highest evaporator temperature obtained for the conventional refrigeration system (CRS) and modified refrigerators system (MRS) were -5oC and 0oC respectively. Interestingly, an efficiency improvement of about 10% was achieved for the MRS. The result shows a remarkable improvement in the COP of the MRS. Therefore, for a better performance, thermal radiation shield can be recommended to be incorporated in vapour compression refrigeration system.